Comparison Between Islamic Law and Positive Law in a Judicial Context - Suprijati Sarib; Syarifuddin; Sabil Mokodenseho (West Science Islamic Studies, 2023)
This study explores Indonesia's complex legal system, which coexists with positive and Islamic law. The study examines how various legal systems apply justice and how people perceive it, using a quantitative research design. When survey data is combined with document analysis, subtle patterns and differences are revealed. The findings show that although positive law places more emphasis on procedural issues and the defense of individual rights, Islamic law views justice as being strongly related to moral and ethical principles. Different views of justice are influenced by differences in demographics. The discussion of these findings' implications within the framework of legal pluralism provides valuable perspectives for researchers, policymakers, and legal practitioners attempting to navigate the intricate legal landscape of Indonesia.